Trust and Purchase Intention Model of Muslim Z-Generation Consumers on E-Commerces (B2C) in Indonesia - Marits, Shofi Arofatul; Zaerofi, Afif (Jurnal Manajemen, 2023)
Indonesia is one of the countries with the highest number of online buyers. One of the potential target markets of e-commerce (B2C) is Z generation, a group of young people who spend most of their time accessing information from websites, including e-commerce. This study aimed to find out the effect of trust and purchasing intention model in the context of online shopping. This study used Structural Equating Modeling (SEM) approach. The sampling technique employed was convenience random sampling with a total of 300 respondents. This study found that perceived trust significantly impacts on purchase intention. Interestingly, perceived risk have negative effect on perceived trust while other variables, namely, product description, perceived site quality, enduring and sitational involvement have a positively effect on perceived trust